Botulism in the Astrakhan region: a retrospective study - G. A. Kharchenko; O. G. Kimirilova; A. A. Kimirilov (LLC "Diagnostics and Vaccines", 2022)
The average number of annually registered cases of botulism in the Russian Federation is 300. At the same time, there is an increase in the number of deaths to 26 per year.Materials and methods. The article presents the results of a clinical and epidemiological analysis of 47 cases of botulism in adults treated at the State Medical Institution «Regional Infectious Clinical Hospital named after A.M. Nichoga» in Astrakhan in the period from 2009 to 2019. The diagnosis of botulism was confirmed by a positive reaction of biological neutralization of the toxin in white mice.Results. It is established that the epidemic process of botulism in the Astrakhan region is characterized mainly by sporadic morbidity in adults of working age and the absence of cases of the disease in children. All patients had food botulism, which occurred typically in the form of moderate and severe forms of the disease, with a mortality rate of 4.2%. There is an increase in the share of fish and fish products, non-industrial preparation, as sources of infection. Laboratory confirmation of botulism occurred in 60% of patients.